The Effect of Rebranding Lays to Customer Loyalty with Brand Image as A Mediation Variable - Hansen Batara; Daniel Susilo (LONTAR: Jurnal Ilmu Komunikasi, 2022)
PT Indofood CBP announced the launch of Chitato Lite, which is a form of the rebranding of Lays products by changing the logo and packaging. This study aims to determine whether there is an effect of Rebranding, Brand Image, and Customer Loyalty and to find out whether Brand Image mediates the effect of Rebranding Lays on Customer Loyalty. This study uses quantitative methods with the type of explanatory research and uses survey methods. The data was obtained by distributing questionnaires to 219 followers of the Instagram accounts @laysindonesia and @mychitato who were aware of the Lays rebranding. The type of sampling used is non-probably sampling with a purposive sampling technique. Hypotheses were tested using normality, correlation, and linearity tests. The results of this study indicate that there is a significant influence between rebranding on customer loyalty directly and indirectly, while the direct effect is 29.3% and the indirect effect of rebranding on customer loyalty through brand image is 43.3%. This shows that Lays' rebranding is considered relevant to product changes.